Empirical Analysis of Labor, Income, and Human Development Influences on Poverty in Central Sulawesi Districts and Cities - Khusnudin Tri Subhi (Universitas Muhammadiyah Palu, 2026)
Central Sulawesi Province has high economic potential, especially in the manufacturing, mining and agricultural sectors. However, this potential has not been able to lift Central Sulawesi Province out of poverty, which is 12.41 percent. This analysis aims to see the effect of labor, per capita income and human quality on poverty in districts and cities of Central Sulawesi Province in 2021–2023 through a panel data regression approach. This study shows that per capita income and the Human Development Index (HDI) have a significant negative effect on district/city poverty, while the Labor Force Participation Rate (LP) variable does not have a significant effect. Per capita income has a “trickle-down” effect that helps alleviate poverty, while a higher HDI is correlated with poverty reduction. The results of this analysis suggest the need for policies that focus on increasing HDI through access to education and health, as well as increasing income/capita through the development of leading economic sectors.